Estimating Water Availability using the SCS-CN Method based on Long Term Hydrologic Simulation and the Geographic Information System - Atie Tri Juniati; Dwita Sutjiningsih; Herr Soeryantono; Eko Kusratmoko (International Journal of Technology, 2019)
Water is one of the main resources for sustainable city development. To ensure the availability of adequate water for human use, water resource managers need to estimate the amounts of water that enter, pass through, and leave individual watersheds. This is a challenge, because the relative magnitudes of the transfers of individual components in the hydrologic cycle can vary greatly. This paper analyses water availability estimation using the modified Soil Conservation Service Curve Number (SCS-CN) model. The model provides a hydrologically sound procedure to better represent capture behaviour. The study focuses on upper catchments located in West Java, Indonesia. Water availability estimation from this catchment area is needed to understand changes in river flow, as it constitutes information for the Indonesian Regional Water Utility Company (Perusahaan Daerah Air Minum (PDAM) Tirta Pakuan) in meeting the clean water needs of Bogor city. The existing SCS-CN model determines the Curve Number (CN) variable using Antecedent Moisture Condition (AMC). Daily moisture storage is updated based on varying the curve number and other hydrologic abstractions. A model was used to estimate stream flow components, direct-surface runoff, base flow, and hydrological abstractions. The calibration results indicate good model performance, with R2 and Nash Sutcliffe efficiency values for simulated monthly data of 0.62 and 0.36, respectively. The model was also successfully validated in the upper Cisadane catchment area by the respective R2 and Nash Sutcliffe efficiency values of 0.65 and 0.42. Validation of the model indicates that it reasonably simulates the catchment response and is suitable for use as a tool in estimating water availability. From these estimates, and in accordance with the data used, it can be concluded that the level of water availability can still meet Bogor's water needs from 2004-2009.